Low-carbon cement-based ultra-high performance concrete and preparation method thereof
By performing acid-lysis, co-precipitation and alkaline activity excitation treatment on construction waste fine powder, it is converted into calcium-aluminum hydrotalcite, and combined with silica calcium enhancement components and retarding components, the application problems of low-carbohydrate cement and construction waste fine powder in ultra-high performance concrete are solved, and ultra-high performance concrete with high density and high mechanical properties are achieved.
Patent Information
- Application Number
- CN202411652684.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-19
AI Technical Summary
The prior art is difficult to take into account the carbonization effect of low-carbon cement while ensuring the high density requirements of ultra-high performance concrete, and at the same time, it is effective to utilize construction waste micro powder, resulting in insufficient mechanical properties and durability.
By acidolysis, coprecipitation and alkaline activity excitation treatment of construction waste micro powder, it is converted into calcium-aluminum hydrotalcite with strong adsorption characteristics, and combined with silicon calcium enhancement components and retarding components, the hydration process is adjusted, sufficient carbonization channels are provided, and the mechanical properties of concrete are improved.
It achieves the improvement of the density and mechanical properties of ultra-high performance concrete while ensuring the carbonization effect of low-carbon cement, enhances the resource utilization of micro powder in construction waste, and improves the environmental significance and durability of concrete.
Smart Images

Figure BDA0005141365170000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and specifically relates to a low-carbon cement-based ultra-high performance concrete and a preparation method thereof. Background Art
[0002] Ultra-high performance concrete (UHPC) is usually designed and prepared using the closest packing theory. Its high density makes it a fiber-reinforced cement-based composite material with ultra-high mechanical properties, durability and toughness. It is widely used in the preparation of large-span pedestrian bridges, highway and railway bridges, thin-walled silos, nuclear waste tanks, cable anchor reinforcement plates, ATM protective shells, etc. With the introduction of the national "dual carbon" policy, the development of green and low-carbon new building materials has become one of the main research hotspots. Ultra-high performance concrete is considered to be an important low-carbon emission engineering structural material due to its high specific strength and durability.
[0003] At present, the preparation of ultra-high performance concrete usually uses ordinary Portland cement and / or Portland cement as the main cementitious material, and the main mineral composition of ordinary Portland cement and / or Portland cement is C2S, C3S, C3A, C4AF, and the main calcium source of these mineral compositions is limestone. The high-temperature decomposition of limestone produces a large amount of CO2, which is contrary to the dual carbon policy promoted by the country. Low-carbon cement is a cement product that can significantly reduce carbon emissions. The carbon dioxide emissions during its production process are 40%-80% lower than those of ordinary cement. Commonly used raw materials include steel slag, fly ash, slag and silicate, and the main mineral composition is 5%-40% C3S2, 20%-50% γ-C2S, and 10%-50% CS. If low-carbon cement can be used to prepare ultra-high performance concrete, it will have very important environmental significance.
[0004] However, although low-carbon cement production has lower carbon emissions, its own hydration activity is low, and the products need to be carbonized to be enhanced. During the carbonization process of low-carbon cement products, the denser the product, the worse the carbonization enhancement effect. However, the preparation of ultra-high performance concrete often requires the product to have a higher density in order to have excellent mechanical properties, durability and toughness. Therefore, when using low-carbon cement for the preparation of ultra-high performance concrete, how to balance the carbonization effect of low-carbon cement and the high density requirements of ultra-high performance concrete is an urgent problem to be solved.
[0005] At the same time, construction waste powder is an issue that cannot be ignored when recycling waste concrete. It accounts for about 5%-20% of the total amount of waste concrete. Its main mineral components are silicon dioxide, calcium hydroxide, calcium sulfonate, calcium aluminosilicate and other potentially active components. However, when construction waste powder is used in concrete preparation, especially ultra-high performance concrete with a low water-binder ratio (usually 0.12-0.18), due to the high water absorption rate and low hydration activity of construction waste powder, the workability of the mixture is poor when concrete is prepared with construction waste powder, and the mechanical properties and durability after hardening are also poor, which greatly limits its resource utilization. If construction waste powder can be successfully used in the preparation of ultra-high performance concrete, it will not only provide a new direction for the resource utilization of construction waste powder, but also increase the low-carbon emission reduction significance of ultra-high performance concrete. Summary of the invention
[0006] In view of the problems existing in the prior art, the present invention provides a low-carbon cement-based ultra-high performance concrete, which takes into account the carbonization effect of low-carbon cement while ensuring the high density requirement of ultra-high performance concrete, and can also realize the resource utilization of construction waste fine powder.
[0007] In order to achieve the above purpose, the technical solutions adopted are as follows:
[0008] A low-carbon cement-based ultra-high performance concrete, comprising the following components by weight:
[0009] 500-600 parts of low-carbon cement, 350-500 parts of silicon-calcium reinforcing components, 150-250 parts of modified recycled construction waste powder, 1,100 parts of fine aggregate, 1.8-2.5 parts of retarding components, 9.5-11.5 parts of water-reducing components, and 240-250 parts of water; steel fiber accounting for 1.5-2.5% of the volume of the low-carbon cement-based ultra-high performance concrete is added; the modified recycled construction waste powder is obtained by acid hydrolysis, co-precipitation, and alkali activity activation of construction waste powder.
[0010] The present invention converts unstable hydration products in the construction waste powder into calcium aluminum hydrotalcite with strong adsorption characteristics by acidolysis, coprecipitation and alkali activity stimulation of the construction waste powder, and stimulates the hydration activity of the construction waste powder, and cooperates with the silicon calcium reinforcement component to make up for the low activity of low carbon cement, resulting in the problem of low strength of the prepared low carbon ultra-high performance wave absorbing concrete. At the same time, the present invention adjusts the silicon calcium reinforcement component and the hydration process of the modified recycled construction waste powder by adding a retarding component, and cooperates with the calcium aluminum hydrotalcite in the modified recycled construction waste powder, while ensuring that the prepared low carbon UHPC has good working performance, providing sufficient carbonization channels for low carbon cement, absorbing more CO2, so as to improve the mechanical properties of the prepared low carbon UHPC. Moreover, based on the above-mentioned material system, the present invention adopts a high water-cement ratio (0.20-0.22) to improve the problem of excessive viscosity of the slurry caused by the high adsorption of the modified recycled construction waste powder, thereby affecting its CO2 absorption efficiency, and providing favorable conditions for the strength enhancement of low carbon UHPC. In addition, the present invention reasonably adjusts the dosage ratio of each component, so that the carbonation of low-carbon cement and the hydration of ordinary Portland cement / Portland cement develop synergistically, further improving the mechanical properties of the entire system.
[0011] Optionally, the modified recycled construction waste powder is prepared by the following method:
[0012] (1) Grind the construction waste powder to a specific surface area of ≥300m 2 / kg, then acid hydrolyze at 50-60℃ and filter to obtain the Ca 2+ 、Al 3+ Solution A and solid B; in this step, the acid solution of the acid hydrolysis may preferably be 15-20% by mass of hydrochloric acid, and the mass ratio of the recycled construction waste powder to the acid solution may preferably be 1: (2-3);
[0013] (2) adding an alkaline solution to the solution A, adjusting the pH of the solution A to 10-11, carrying out a coprecipitation reaction at 80-90° C., followed by crystallization at 100-110° C., cooling, filtering, washing, and drying to obtain calcium aluminum hydrotalcite and a filtrate C; in this step, the alkaline solution may preferably be a sodium hydroxide solution, and the molar concentration of the sodium hydroxide solution may preferably be 0.1-0.2 mol / L;
[0014] (3) mixing the solid B and the filtrate C, reacting with alkali at 40-60° C. for 3-5 hours, filtering, and drying to obtain micropowder D;
[0015] (4) The calcium aluminum hydrotalcite and the fine powder D are mixed to obtain modified recycled construction waste fine powder.
[0016] The present invention uses an acid hydrolysis method to decompose the unstable hydration products in the recycled construction waste micropowder, and then uses a coprecipitation method to separate the Ca2+ 、Al 3+ The present invention is converted into calcium-aluminum hydrotalcite, wherein the calcium-aluminum hydrotalcite, as a layered structure material, can absorb water and gas, and can not only be used as a CO2 collector, but also provide a carbonization channel for CO2, thereby providing enhanced protection for the application of low-carbon cement in ultra-high performance concrete. At the same time, the present invention makes full use of the filtrate (alkaline solution) produced by the co-precipitation reaction and the filtrate (solid B) produced by the acid hydrolysis reaction. The alkaline filtrate can stimulate the chemical activity of solid B, thereby effectively improving the reaction activity of recycled construction waste micropowder and cement, thereby effectively ensuring the mechanical properties of low-carbon ultra-high performance absorbing concrete.
[0017] Optionally, the silica-calcium reinforcing component consists of ordinary Portland cement or Portland cement and silica fume; the mass ratio of the ordinary Portland cement or Portland cement to the silica fume is 1:(0.2-0.3).
[0018] The present invention uses ordinary Portland cement or Portland cement and silica fume as reinforcing components of the entire system. The hydration rate of ordinary Portland cement or Portland cement and silica fume is faster than that of low carbon cement, which can make up for the problem that when low carbon cement is used to prepare casting concrete, the hydration activity is low, resulting in slow hardening and coagulation of the slurry and a long demolding period. In addition, the calcium hydroxide produced by the hydration of ordinary Portland cement or Portland cement can balance the overall alkalinity of the slurry, avoiding the substantial reduction of the alkalinity of the slurry due to the carbonization of the low carbon cement, which leads to rust of the steel fiber and affects the durability and conductive wave absorbing performance of the low carbon ultra-high performance absorbing concrete.
[0019] Optionally, the grade of the ordinary Portland cement or Portland cement is not less than grade 42.5.
[0020] Optionally, the water demand ratio of the silica fume is not greater than 125%, and the 28d activity index is not less than 105%.
[0021] Optionally, the retarding component is formed by mixing sodium gluconate and tartaric acid in a mass ratio of 1:(0.1-0.3).
[0022] Optionally, the water reducing component is a polycarboxylic acid water reducing agent having a water reducing rate of not less than 25%.
[0023] Optionally, the steel fiber has a diameter of 0.18-0.22 mm, a length of 13-15 mm, and an aspect ratio of 60-70.
[0024] Optionally, the fine aggregate is one or more of quartz sand, river sand, and machine-made sand, wherein the quartz sand preferably has a fineness modulus of 1.8-2.0, and the river sand and machine-made sand preferably have a fineness modulus of 2.3-2.5.
[0025] Optionally, the main components of the low carbon cement include 23.5-25.5% C3S2, 31.5-34.5% C2S, 19.5-22.5% CS, and 20.0-24.0% C3S by mass percentage, and the specific surface area of the low carbon cement is not less than 300m 2 / kg.
[0026] The second object of the present invention is to provide a method for preparing the above-mentioned low-carbon cement-based ultra-high performance concrete, the preparation method comprising the following steps:
[0027] 1) After the low carbon cement, the silicon-calcium reinforcing component, the modified recycled construction waste powder, the fine aggregate, the retarding component, and the water reducing component are uniformly mixed, the water is added and stirred into a slurry, and then the steel fiber is added to the slurry and stirred for 1-2 minutes to obtain a low carbon cement-based ultra-high performance concrete slurry precursor;
[0028] 2) In a closed environment, a certain amount of CO2 gas is charged into the low-carbon cement-based ultra-high performance concrete slurry precursor while stirring, and the mixture is poured, formed, demolded, and cured to obtain low-carbon cement-based ultra-high performance concrete, wherein the amount of CO2 gas charged can preferably be 4-6% of the mass of the cementitious material.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The present invention innovatively uses low-carbon cement and construction waste powder simultaneously for the preparation of ultra-high performance concrete, which solves the problem that low-carbon cement and construction waste powder are difficult to use for the preparation of ultra-high performance concrete, greatly improves the environmental significance of ultra-high performance concrete, and is also conducive to its promotion and application.
[0031] The low-carbon cement-based ultra-high performance concrete prepared by the present invention has good working performance, mechanical properties and durability, its expansion is ≥600mm, its 28d compressive strength can reach more than 120MPa, and its chloride ion permeability resistance coefficient can be less than 17.0×10 -14 m 2 ·s -1 Moreover, during the entire preparation process of low-carbon cement-based ultra-high performance concrete, the CO2 storage rate can reach more than 20%. DETAILED DESCRIPTION
[0032] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with specific embodiments, but the content of the present invention is not limited to the following embodiments.
[0033] The specific implementation method provides a modified recycled construction waste powder:
[0034] The construction waste powder is ball-milled to a specific surface area of 350m 2 / kg, according to the mass ratio of 1:2, the ball-milled recycled construction waste powder was placed in 15% hydrochloric acid and acid-lyzed at 50°C. After the acid-lysate was completed, it was filtered to obtain the Ca-containing 2+ 、Al 3+ Solution A and solid B;
[0035] A sodium hydroxide solution with a molar concentration of 0.15 mol / L is added to solution A, the pH of solution A is adjusted to 10, a coprecipitation reaction is carried out at 85° C., and then, crystallization is carried out at 100° C., cooling, filtering, washing, and drying to obtain calcium aluminum hydrotalcite and filtrate C;
[0036] The solid B and the filtrate C were mixed, and the reaction was alkali-induced at 50°C for 3 hours, filtered, and dried to obtain micro powder D;
[0037] The calcium aluminum hydrotalcite and the powder D are mixed to obtain modified recycled construction waste powder.
[0038] Raw materials used in the specific implementation manner:
[0039] The main mineral composition of low carbon cement is calculated by mass percentage, including: 24.8% C3S2, 33.2% C2S, 21.0% CS, 21.0% C3S. The specific surface area of the low carbon cement is 325m 2 / kg. The calcium-silicon reinforcement component is composed of P·O52.5 ordinary Portland cement and silica fume in a mass ratio of 1:0.2, the water demand ratio of silica fume is 115%, and the 28d activity index is 118%. The fine aggregate is quartz sand with a fineness modulus of 1.9. The retarding component is a mixture of sodium gluconate and tartaric acid in a mass ratio of 1:0.2. The water-reducing component is a powdered polycarboxylic acid water-reducing agent with a water-reducing rate of 25%. The average diameter of the steel fiber is 0.20 mm, the average length is 14 mm, and the average aspect ratio is 70. Unless otherwise specified, the remaining raw materials are commercially available.
[0040] Example 1
[0041] A low-carbon cement-based ultra-high performance concrete comprises, by weight: 500 parts of low-carbon cement, 500 parts of silicon-calcium reinforcing components, 150 parts of modified recycled construction waste powder, 1,100 parts of fine aggregate, 2.5 parts of retarding components, 9.5 parts of water-reducing components, 250 parts of water, and steel fibers accounting for 2.0% of the volume of the low-carbon cement-based ultra-high performance concrete.
[0042] The above-mentioned low-carbon cement-based ultra-high performance concrete is specifically prepared by the following method:
[0043] 1) According to the above dosage ratio, low carbon cement, silicon-calcium reinforcing component, modified recycled construction waste powder, fine aggregate, retarding component and water reducing component are mixed evenly, and water is added to stir into slurry, and then steel fiber is added to the slurry and stirred for 2 minutes to obtain a low carbon cement-based ultra-high performance concrete slurry precursor;
[0044] 2) In a closed environment, 5% of the mass of the cementitious material is charged into the low-carbon cement-based ultra-high performance concrete paste precursor with CO2 gas (concentration of 99.9%) while stirring, wherein the CO2 charging time is 90 seconds, and then the mixture is poured, formed, and demolded, and the specimens after demolding are subjected to standard curing to a specified age to obtain low-carbon cement-based ultra-high performance concrete.
[0045] Example 2
[0046] The low-carbon cement-based ultra-high performance concrete of this embodiment includes the following components by weight: 550 parts of low-carbon cement, 450 parts of silicon-calcium reinforcing component, 200 parts of silicon-modified recycled construction waste powder, 1100 parts of fine aggregate, 2.2 parts of retarding component, 10 parts of water-reducing component, 245 parts of water, and steel fiber accounting for 2.0% of the volume of the low-carbon cement-based ultra-high performance concrete. The preparation method is the same as that of Example 1.
[0047] Example 3
[0048] The difference between this embodiment and embodiment 1 is that the low-carbon cement-based ultra-high performance concrete of this embodiment includes the following components, by weight: 550 parts of low-carbon cement, 400 parts of cement reinforcing component, 250 parts of modified recycled construction waste powder, 1100 parts of fine aggregate, 2.0 parts of retarding component, 11.5 parts of water-reducing component, 240 parts of water, and steel fiber accounting for 2.0% of the volume of the low-carbon cement-based ultra-high performance concrete.
[0049] Example 4
[0050] The low-carbon cement-based ultra-high performance concrete of this embodiment includes the following components by weight: 600 parts of low-carbon cement, 350 parts of silicon-calcium reinforcing component, 150 parts of modified recycled construction waste powder, 1100 parts of fine aggregate, 1.8 parts of retarding component, 9.5 parts of water-reducing component, 245 parts of water, and steel fiber accounting for 2.0% of the volume of the low-carbon cement-based ultra-high performance concrete. The preparation method is the same as that of Example 1.
[0051] Comparative Example 1
[0052] In the low-carbon cement-based ultra-high performance concrete of this comparative example, unmodified recycled construction waste powder is used, and the construction waste powder is only ball-milled to a specific surface area of 350m 2 / kg, and the rest is the same as in Example 1.
[0053] The above-mentioned low-carbon cement-based ultra-high performance concrete is specifically prepared by the following method:
[0054] 1) According to the above dosage ratio, low carbon cement, calcium silicon reinforcement component, construction waste powder, fine aggregate, retarding component and water reducing component are mixed evenly, and water is added to stir into slurry, and then steel fiber is added to the slurry and stirred for 2 minutes to obtain a low carbon cement-based ultra-high performance concrete slurry precursor;
[0055] 2) In a closed environment, 5% of the mass of the cementitious material is charged into the low-carbon cement-based ultra-high performance concrete paste precursor with CO2 gas (concentration of 99.9%) while stirring, wherein the CO2 charging time is 90 seconds, and then the mixture is poured, formed, and demolded, and the specimens after demolding are subjected to standard curing to a specified age to obtain low-carbon cement-based ultra-high performance concrete.
[0056] Comparative Example 2
[0057] The low carbon cement-based ultra-high performance concrete of this comparative example does not contain any retarding component, and the rest is the same as in Example 1.
[0058] The above-mentioned low-carbon cement-based ultra-high performance concrete is specifically prepared by the following method:
[0059] 1) According to the above dosage ratio, low carbon cement, silicon-calcium reinforcing component, modified recycled construction waste powder, fine aggregate, and water-reducing component are mixed evenly, and water is added to stir into slurry, and then steel fiber is added to the slurry and stirred for 2 minutes to obtain a low carbon cement-based ultra-high performance concrete slurry precursor;
[0060] 2) In a closed environment, 5% of the mass of the cementitious material is charged into the low-carbon cement-based ultra-high performance concrete paste precursor with CO2 gas (concentration of 99.9%) while stirring, wherein the CO2 charging time is 90 seconds, and then the mixture is poured, formed, and demolded, and the specimens after demolding are subjected to standard curing to a specified age to obtain low-carbon cement-based ultra-high performance concrete.
[0061] Comparative Example 3
[0062] The retarding component in the low-carbon cement-based ultra-high performance concrete of this comparative example is only sodium gluconate, and the rest is the same as in Example 1.
[0063] The above-mentioned low-carbon cement-based ultra-high performance concrete is specifically prepared by the following method:
[0064] 1) According to the above dosage ratio, low carbon cement, silicon-calcium reinforcing component, modified recycled construction waste powder, fine aggregate, retarding component and water reducing component are mixed evenly, and water is added to stir into slurry, and then steel fiber is added to the slurry and stirred for 2 minutes to obtain a low carbon cement-based ultra-high performance concrete slurry precursor;
[0065] 2) In a closed environment, 5% of the mass of the cementitious material is charged into the low-carbon cement-based ultra-high performance concrete paste precursor with CO2 gas (concentration of 99.9%) while stirring, wherein the CO2 charging time is 90 seconds, and then the mixture is poured, formed, and demolded, and the specimens after demolding are subjected to standard curing to a specified age to obtain low-carbon cement-based ultra-high performance concrete.
[0066] Comparative Example 4
[0067] The low-carbon cement-based ultra-high performance concrete of this comparative example does not contain any cement reinforcing component, and uses low-carbon cement to replace the cement reinforcing component. The rest is the same as in Example 1.
[0068] The above-mentioned low-carbon cement-based ultra-high performance concrete is specifically prepared by the following method:
[0069] 1) According to the above dosage ratio, low carbon cement, modified recycled construction waste powder, fine aggregate, retarding component and water reducing component are uniformly mixed, and water is added to stir into slurry, and then steel fiber is added to the slurry and stirred for 2 minutes to obtain a low carbon cement-based ultra-high performance concrete slurry precursor;
[0070] 2) In a closed environment, 5% of the mass of the cementitious material is charged into the low-carbon cement-based ultra-high performance concrete paste precursor with CO2 gas (concentration of 99.9%) while stirring, wherein the CO2 charging time is 90 seconds, and then the mixture is poured, formed, and demolded, and the specimens after demolding are subjected to standard curing to a specified age to obtain low-carbon cement-based ultra-high performance concrete.
[0071] According to the standard specification of ultra-high performance concrete, the working performance, mechanical properties and durability performance of the low-carbon cement-based ultra-high performance concrete of Examples 1-4 of the present invention and Comparative Examples 1-4 were tested. The test results are shown in Table 1.
[0072] The mass loss of the test piece between 400-900°C was tested by differential scanning calorimetry analysis method, and the mass loss was recorded as the CO2 absorption amount. The CO2 storage rate was then calculated by the CO2 absorption amount and the CO2 charging amount. CO2 storage rate = CO2 absorption amount / CO2 charging amount × 100%. The calculation results are shown in Table 1.
[0073] It can be seen from Table 1 that the low-carbon cement-based ultra-high performance concrete prepared in the present invention has good working performance, its 28d compressive strength can reach more than 120MPa, and its chloride ion permeability resistance coefficient is not more than 17.0×10 -14 m 2 ·s -1At the same time, compared with comparative example 1, after the construction waste powder is modified in Example 1 of the present invention, the mechanical properties and durability are greatly improved, among which the 28d compressive strength is increased by 27.7%, and the flexural strength is increased by 71.7%; compared with comparative example 2, the addition of an appropriate amount of retarder in Example 1 of the present invention can greatly improve the initial working performance of the slurry after CO2 is introduced, and the addition of the retarder is beneficial to the carbonization and hardening efficiency of the slurry, and further to the improvement of the mechanical properties and durability of the hardened slurry, among which the 28d compressive strength is increased by 27.7%, and the flexural strength is increased by 71.7%. The flexural strength is increased by 20.0% and 52.8% respectively; relative to comparative example 3, in embodiment 1 of the present invention, the ammonium gluconate and tartaric acid mixture is used as the retarding component, which can improve the initial fluidity of the slurry, and the 28d compressive strength can be increased by 16.8%, and the flexural strength is increased by 31.1%; relative to comparative example 4, in embodiment 1 of the present invention, the cement reinforcing component is added, which can greatly improve the mechanical properties of the hardened slurry, wherein the 28d compressive strength is increased by 250.1%, the flexural strength is increased by 198.5%, and the durability is also significantly improved.
[0074] Table 1
[0075]
[0076]
[0077] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A low-carbon cement-based ultra-high performance concrete, characterized in that The following components are included by weight: 500-600 parts of low-carbon cement, 350-500 parts of silicon-calcium reinforcing components, 150-250 parts of modified recycled construction waste powder, 1,100 parts of fine aggregate, 1.8-2.5 parts of retarding components, 9.5-11.5 parts of water-reducing components, and 240-250 parts of water; steel fiber accounting for 1.5-2.5% of the volume of the low-carbon cement-based ultra-high performance concrete is added; the modified recycled construction waste powder is obtained by acid hydrolysis, co-precipitation, and alkali activity activation of construction waste powder.
2. The low carbon cement-based ultra-high performance concrete according to claim 1, characterized in that The modified recycled construction waste powder is prepared by the following method: (1) Grind the construction waste powder to a specific surface area of ≥300m 2 / kg, then acid hydrolyze at 50-60℃ and filter to obtain the Ca 2 + 、Al 3+ Solution A and solid B; (2) adding an alkaline solution to the solution A, adjusting the pH of the solution A to 10-11, carrying out a coprecipitation reaction at 80-90° C., then crystallizing at 100-110° C., cooling, filtering, washing, and drying to obtain calcium aluminum hydrotalcite and a filtrate C; (3) mixing the solid B and the filtrate C, reacting with alkali at 40-60° C. for 3-5 hours, filtering, and drying to obtain micropowder D; (4) The calcium aluminum hydrotalcite and the fine powder D are mixed to obtain modified recycled construction waste fine powder.
3. The low carbon cement-based ultra-high performance concrete according to claim 1, characterized in that The silica-calcium reinforcement component consists of ordinary silicate cement or silicate cement and silica fume; the mass ratio of the ordinary silicate cement or silicate cement to the silica fume is 1:(0.2-0.3).
4. The low carbon cement-based ultra-high performance concrete according to claim 3, characterized in that The grade of the ordinary Portland cement or Portland cement is not less than 42.5; the water demand ratio of the silica fume is not more than 125%, and the 28d activity index is not less than 105%.
5. The low carbon cement-based ultra-high performance concrete according to claim 1, characterized in that The retarding component is prepared by mixing sodium gluconate and tartaric acid in a mass ratio of 1:(0.1-0.3).
6. The low carbon cement-based ultra-high performance concrete according to claim 1, characterized in that The water reducing component is a polycarboxylic acid water reducing agent with a water reducing rate of not less than 25%.
7. The low carbon cement-based ultra-high performance concrete according to claim 1, characterized in that The steel fiber has a diameter of 0.18-0.22 mm, a length of 13-15 mm, and an aspect ratio of 60-70.
8. The low carbon cement-based ultra-high performance concrete according to claim 1, characterized in that The fine aggregate is one or more of quartz sand, river sand and machine-made sand.
9. The low carbon cement-based ultra-high performance concrete according to claim 1, characterized in that The main components of the low carbon cement include 23.5-25.5% C3S2, 31.5-34.5% C2S, 19.5-22.5% CS, and 20.0-24.0% C3S by mass percentage. The specific surface area of the low carbon cement is not less than 300m 2 / kg.
10. The method for producing low carbon cement-based ultra-high performance concrete according to any one of claims 1 to 9, characterized in that The steps include: 1) After the low-carbon cement, the silicon-calcium reinforcing component, the modified recycled construction waste powder, the fine aggregate, the retarding component, and the water-reducing component are uniformly mixed, the water is added and stirred into a slurry; the steel fiber is added to the slurry and the stirring is continued for 1-2 minutes to obtain a low-carbon cement-based ultra-high performance concrete slurry precursor; 2) In a closed environment, CO2 gas is charged into the low-carbon cement-based ultra-high performance concrete slurry precursor while stirring, and pouring, molding, demolding, and curing are performed to obtain low-carbon cement-based ultra-high performance concrete.
Citation Information
Patent Citations
All-solid waste material, and preparation method and application thereof
CN113105202A
Low-carbon green ultra-high performance concrete and preparation method thereof
CN114368953A
Low-carbon cement concrete and preparation method thereof
CN114873979A
Ultra-high performance concrete and preparation method thereof
CN118047562A
Ultra-high performance nano-modified concrete composition with borosilicate glass lamp waste powder
EP2837609A1